Perbandingan Kadar Albumin Ikan Gabus (Channa striata) dari Proses Perebusan dan Pengukusan dengan Menggunakan Uji Biuret: Comparison of Cork Fish (Channa striata) Albumin Content from Boiling and Steaming Process by Using Biuret Test - Sulfitri Suardi; Syaiful Bahri; Khairuddin; Ni Ketut Sumarni; Erwin Abdul Rahim (KOVALEN: Jurnal Riset Kimia, 2020)
Cork Fish (Channa striata) is a freshwater fish that was spread throughout most of Indonesia and it contains albumin that was beneficial to the human body. Albumin was easily dissolved in water during the cooking process both boiled and steamed. This study aims to determine the influence of boiling and steaming times at 100oC against albumin content of cork fish that lost and left in fish meat. The times of boiling and steaming that was used to processing the fish were 10, 15, and 20 minutes. The albumin concentration that lost and left in for the boiling and the steaming process was determined by the biuret test that used a UV-Vis spectrophotometer at albumin maximum wavelength of 530 nm. The results showed that albumin content that lost for 10 minutes boiling process (62 mg/10g) was smaller than the other boiling times and albumin left in fish meat was 164 mg/10g. The same result was also obtained at 10 minutes steaming process which results left in albumin content of 167 mg/10g and lost albumin of 62 mg/10g. The albumin content that lost or dissolved in water for the steaming process was smaller than the boiling process, therefore the steaming process is more efficient than the boiling process at cork fish processing. Keywords: Cork fish, albumin, boiling, steaming.